Efficacy of the argon plasma coagulation in patients with weight regain after gastric bypass: a randomized control trial - Gurian, Gustavo Carvalho; Watanabe, Lígia Moriguchi; Nonino, Carla Barbosa; Barato, Mariana; Ferreira-Julio, Maysa Araújo; Arantes, Francisco Alves; Sivieri, Thiago; Noronha, Natália Yumi; Souza, Dorotéia Silva Rossi; Fernandes-Ferreira, Rafael; Pinhel, Marcela Augusta de Souza (Endoscopy International Open, 2023)
Background and study aims Endoscopic procedure using argon plasma coagulation (APC) promotes a progressive reduction in gastrojejunal anastomosis diameter. The present study aimed to evaluate the efficacy of the APC in patients with weight regain in the postoperative periods of gastric bypass.Patients and methods This was a randomized controlled trial conducted with 66 patients who were randomly assigned selected (using lottery method) and divided into two groups: study group (SG), 38 patients (APC treatment); and control group (CG), 28 patients (only endoscopy procedure). We considered 30 days,180 days, and one year as short-term, medium-term, and long-term, respectively. The parameters analyzed were total weight loss (TWL), excess weight loss (%EWL), total weight loss (%TWL), and reduction of weight regain (%RWR). Furthermore, a biopsy for neoplastic histological changes was carried out for the APC group. For statistical analysis, values of P < 0.05 were considered significant.Results The %TWL and %RWR were higher in the SG in short, medium, and long terms, when compared to the same periods in the CG (P < 0.001). One year after follow-up, the final weight did not reach the statistical difference between groups. Biopsy performed in SG 1 year after APC did not reveal neoplastic histological changes.Conclusions APC effectively treats weight regain after bariatric surgery in the short and medium-term. An important "new" weight gain was observed in the long-term, showing that obesity is a chronic disease that requires multidisciplinary and family care for life. Also, APC is a safe procedure with low adverse event rates.